(untitled) (Research, Society and Development, 2022)
The study aimed to report the experience of academics who are members of the Tutorial Education Program of the undergraduate Nursing course of a public university located in the south of the country, to the realization of the self-care workshop through integrative and complementary health practices, developed in the online modality, during the Covid-19 pandemic, with the general public. In this context and in view of the complications to the well-being of many individuals, an alternative was sought to encourage and assist in changing this scenario. Therefore, it was found in this activity, carried out online by the Even3 and Youtube platforms, the possibility of guaranteeing the promotion of health in different audiences, enabling the sharing of knowledge and the realization of Integrative and Complementary Practices in Health even during the social distancing. In the workshop, Ayurveda, Aromatherapy, Phytoenergetics, Self-massage and Foot bath were discussed, allowing the integration of theory and practice. The development of the space that promotes health and well-being proved to be satisfactory and provided an opportunity for the exchange of knowledge, the development of skills by students, as well as the reduction of social distance in an online and safe way.